Progress Monitoring of Language Acquisition and Academic Content for English Learners. Issue 3 (28th July 2022) - Rivera, Mabel O.; McKeithan, Glennda K.
Abstract: Meeting the needs of English learners (ELs) effectively must be an individualized, purposeful, and data‐driven process. Progress monitoring can help practitioners to target their EL students' most significant academic and linguistic needs and, subsequently, develop and deliver instructional programming that may help students develop to their fullest potential with regards to language acquisition as well as content knowledge. This article offers considerations of best practices for educators in K–12 settings interested in learning more about progress monitoring of the academic and language proficiency of ELs receiving instruction in varied settings. Considerations regarding progress monitoring for ELs are reviewed, and tables of resources for instructional activities and supporting materials are provided.